RANCANG BANGUN PEMROGRAMAN BERBASIS SISTEM CERDAS UNTUK PENGATURAN PENGISIAN BATERE PEMBANGKIT LISTRIK TENAGA SURYA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2018)
Hydroelectric solar energy Photovoltaic/Solar in addition can be used to program the rural electricity, solar energy utilization opportunities such as street lighting lamps as well as for the survival of the industry and small and medium enterprises. At solar power plants is also still there needs to be some development in managementcharging, this needs to be done in order for the resulting damage to the quality of mecegah power, namely the irregular voltage too high and sometimes too low from the solar cells towards the battery. Solar power plant comprises a PV panel change sunlight into direct current (DC), charging circuits for charging the battery, the charger system served as the heart of electric power generation system of solar power, which the battery used for electric power storage. This study is develop an intelligent system software architecture for Solar Charger Controler and used to arrange direct current to disuply battery by solar energy and transmitted to the load-based fuzzy logic. This simulation is expected to be implemented in a tool that serves as a charging in excess of set flush from the solar panel to batterybased fuzzy. Solar Charger controler based Fuzzy logic can be applied automatically regulates battery charging battery charging and limit if the voltage at the battery with charging function and organize the liberation of current from the battery to the load. software used In this study is Matrix Laboratory (MATLAB) used to simulate fuzzy logic controller as a regulator of the output voltage of boost converter after the solar cells. And managed to simulate the control of the voltage and current that entered the battery, battery filling in the range of 95%.